2009
DOI: 10.1111/j.1440-1819.2008.01898.x
|View full text |Cite
|
Sign up to set email alerts
|

Health service utilization in patients with major depression and co‐morbid pain

Abstract: Aims: Patients with depression often have co-morbid pain symptoms. However, rates of service utilization by psychiatric in-patients with co-morbid pain symptoms are unknown. The purpose of this study is to estimate whether patients with major depression and co-morbid pain access medical treatment for their pain as much as their counterparts with psychiatric diagnoses other than major depression.Methods: A total of 103 patients (62 female; 41 male) were assessed for a diagnosis of major depression applying a ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…A poor health status, bodily pains and psychosomatic symptoms were linked with depressive symptoms. The study subjects reported long-lasting physical pains paralleling to the study of Alvarenga et al [8] of patients with MDD and pain. Indeed, depression complicates the treatment of patients with pain, and vice versa [12,17].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…A poor health status, bodily pains and psychosomatic symptoms were linked with depressive symptoms. The study subjects reported long-lasting physical pains paralleling to the study of Alvarenga et al [8] of patients with MDD and pain. Indeed, depression complicates the treatment of patients with pain, and vice versa [12,17].…”
Section: Discussionsupporting
confidence: 52%
“…One of the most common ailments of depressive patient in primary care is bodily pain. This association is bi-directional [8,9]. Also somatisation, distress [10] and anxiety have a role in pain complaints [11], but depression has been shown to be the most detrimental to quality of life, ability to function [12] and overall health among chronic physical diseases [13].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic pain conditions are associated with substantial disability and costs to the individual and to the health care system (1, 2), which is related in part to the high prevalence of concomitant depression (3–5). Comorbid depression has been associated with reduced adherence by patients to effective pain interventions (6, 7), as well as with reduced effectiveness of these therapies when used (8).…”
Section: Introductionmentioning
confidence: 99%
“…Results and effect sizes are reported in Table T2 2. There were significant group by time interactions for the primary outcome measures (PHQ-9: F [3,191.03] = 9.82, P < 0.001 and K-10: F [3,190.06] = 6.37, P < 0.001). Posttreatment scores were significantly lower in the iCBT group relative to TAU on the primary outcomes, with a large between-group effect size for PHQ-9 scores (Hedges g = 1.01, 95% confidence interval [95% CI] 0.47, 1.54) and a medium effect size for the K-10 (Hedges g = 0.75, 95% CI 0.23, 1.28).…”
Section: Resultsmentioning
confidence: 97%
“…Approximately 1 in 5 adults with OA experience depressed mood (3)(4)(5)(6). Due to increases in life expectancy, obesity, sedentary lifestyle, and an aging population, OA is the fastest growing major health condition worldwide (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%